Efficacy of Red Cell Salvage Systems in Open Acetabular Surgery. (2nd June 2022) - MacDonald, S.; Byrd, C.; Barlow, E.; Nahar, V. K.; Martin, J.; Krenk, D.
Abstract : Over the past 50 years, treatment of displaced acetabular fractures has moved away from conservative treatment with bedrest to operative intervention to achieve anatomic reduction, stable fixation, and allow early range of motion of the hip. However, operative fixation is not without complications. Internal fixation of traumatic acetabular fractures has been coupled with large volume of blood loss both at the time of injury and surgery. This often results in the need for allogenic blood products, which has been linked to increase morbidity (Vamvakas and Blajchman, 2009). In an attempt to avoid the risk associated with allogenic blood transfusion numerous techniques and methods have been devised. Red blood cell salvage (CS) is an intraoperative blood salvage tool where blood is harvested from the operative field. It is washed to remove the plasma, white blood cells, and platelets. The red cells are resuspended in a crystalloid solution. If the hematocrit of the resuspended red blood cells is sufficient, it is transfused to the patient intravenously. The benefits of CS in major spine surgery, bilateral knee replacement, and revision hip surgery are well established (Goulet et al. 1989, Gee et al. 2011, Canan et al. 2013). However, literature reviewing the use of cell saver in orthopedic trauma surgery, specifically acetabular surgery is limited. Our institute performed a retrospective review of 63 consecutive operative acetabular fractures at a level one trauma center. Our study revealed that patients with blood loss of less than 400 mL were 13 times less likely to receive autologous blood, and patients with hemoglobin less than 10.5 were 5 times less likely to receive autologous transfusion (p < 0.05 ). We also found that no patients with a hemoglobin level less than 10.5 and EBL less than 400 mL received autologous blood return. Autologous blood transfusion had no effect on volume or rate of allogenic blood transfusion. We believed that if a patient's preoperative hemoglobin is less than 10.5 or expected blood loss is less than 400 mL, then CS should have a very limited role, if any, in the preoperative blood conservation strategy. We found ASA greater than 2, BMI greater than 24 and associated fracture type to be a risk factor for high blood loss.